Achieving the 2025 WHO global health body-mass index targets: a modelling study on progress of the 53 countries in the WHO European region. (November 2016) - Pineda, Elisa; Sanchez-Romero, Luz Maria; Brown, Martin; Jaccard, Abbygail; Webber, Laura; Jewell, Jo; Breda, João
Abstract: Background: Obesity in the European region has more than tripled since 1980, making it one of the 21st century's main public health challenges. To monitor the prevention and control of major non-communicable diseases (NCDs) WHO and its member states designed an NCD global monitoring framework in which countries agreed to halt obesity levels by 2025. To monitor the feasibility of achieving this goal, we aimed to project the future trends of obesity (body-mass index [BMI] ≥30 kg/m 2 ) to 2025 for each of the 53 WHO European Region Member States. Methods: We extrapolated past BMI trends using a non-linear, multivariate, categorical regression model to estimate country-specific projected prevalence of obesity in adults by 2025. We fitted the model to both measured and self-reported data from cross-sectional country-specific BMI data from nationally representative surveys collected between 1990 and 2015. BMI data were obtained from the WHO BMI database, country statistical databases, health reports, and information collected via personal communication. Findings: By 2025, obesity is predicted to increase in 44 countries. If present trends continue, 33 of the 53 countries will have an obesity prevalence of 20% or more. The highest projected obesity prevalence is predicted for Ireland (43%, 95% CI 28–58). The smallest absolute increase in the projected obesity prevalence from 2015 to 2025 was in Finland (20% by 2025, 95% CI 11–29), Lithuania (24%, 10–38), and the Netherlands (14%, 10–18), each of them with an estimated absolute increase in obesity prevalence of 2% by 2025. Interpretation: Despite efforts from governments, the prevalence of obesity in the European region continues to increase, and with it the health and economic burden of its associated diseases. This paints a concerning picture of the future burden of obesity-related NCDs across the region. Greater and continued effort for the implementation of effective preventive policies and interventions is required from governments if they are to halt obesity prevalence in 10 years'. The data presented by this study could be used to assess or set country-specific obesity reduction targets, as well as provide leverage for investment in obesity prevention and monitoring programmes. Funding: WHO Regional Office for Europe.